2014
DOI: 10.1021/la5015219
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics and Thermodynamics of Nanoparticle Interactions with Plasma and Endosomal Membrane Lipids in Cellular Uptake and Endosomal Escape

Abstract: To be effective for cytoplasmic delivery of therapeutics, nanoparticles (NPs) taken up via endocytic pathways must efficiently transport across the cell membrane and subsequently escape from the secondary endosomes. We hypothesized that the biomechanical and thermodynamic interactions of NPs with plasma and endosomal membrane lipids are involved in these processes. Using model plasma and endosomal lipid membranes, we compared the interactions of cationic NPs composed of poly(d,l-lactide-co-glycolide) modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 36 publications
(76 reference statements)
2
40
0
Order By: Relevance
“…Furthermore, previous studies have also shown that chitosan inhibits cell proliferation and metastases, as well as induces apoptosis (Hasegawa et al, 2001;Kim et al, 2013). The cationic nature of LACPEG could also enhance the cellular uptake of the carrier (Peetla et al, 2014), which could, in turn, increase these effects.…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…Furthermore, previous studies have also shown that chitosan inhibits cell proliferation and metastases, as well as induces apoptosis (Hasegawa et al, 2001;Kim et al, 2013). The cationic nature of LACPEG could also enhance the cellular uptake of the carrier (Peetla et al, 2014), which could, in turn, increase these effects.…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…22,35–37 Therefore, understanding the mechanism of cell penetration (or cellular uptake) of these CPP-induced condensed complexes as well as the mechanisms of escape of these nonviral gene vectors from endosomal compartments is essential for designing efficient CPP/pDNA vectors. 2,38,39 …”
Section: Introductionmentioning
confidence: 99%
“…Confocal imaging data using membrane and endosomal markers demonstrated significantly greater uptake and escape of nanoparticles in sensitive cells than in resistant cells, as membrane rigidity of resistant cells affected the uptake and subsequent escape of nanoparticles from endosomes. 38 …”
Section: Discussionmentioning
confidence: 99%